PENGARUH BUDAYA ORGANISASI, SELF EFFICACY DAN KOMPETENSI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KINERJA KARYAWAN BAGIAN PRODUKSI DI PT. INDOPRIMA GEMILANG SURABAYA - Atik Herawati; M. Shihab; Wardah Wardah (STIE Mahardhika, 2020)
The purpose of this study was to analys the impact of organizational culture, self-efficacy and competence on Organizational Citizenship Behavior (OCB) and job performance of Production Department employees at PT. Indoprima Gemilang Surabaya. A structured questionnaire disseminated to 120 employees as sample, sampling method using random system. Analyzed using SEM with Amos v.24. The results of this study indicate that organizational culture and self-efficacy have a significant on Organizational Citizenship Behavior (OCB); no significant competence on Organizational Citizenship Behavior (OCB); the results also showed that organizational culture, self-efficacy and competence significantly influence employee performance in the Production section of PT. Indoprima Gemilang Surabaya.